Drivers of the real effective exchange rates in high and upper-middle income countries - Vogiazas, Sofoklis; Alexiou, Constantinos; Ogan, Orafiri C. (Wiley, 2018)
This paper revisits the nexus between real effective exchange rate (REER) and total factor productivity (TFP) by controlling for trade openness, financial development and natural resources rents. We use a sample of 60 high‐income and upper‐middle income countries over the period 1995–2015 and employ the GMM estimation framework. Our results advance the empirical knowledge on the drivers of REER by providing robust evidence that the impact of TFP is not uniform across different country clusters. We find that in high‐income countries, increasing productivity causes the REER to depreciate hence becoming more trade competitive while the opposite is true for upper‐middle income countries. Furthermore, financial development and natural resources rents have no meaningful impact in the case of upper‐middle income countries but retain a significant effect in high‐income countries. Trade openness plays a key role in explaining the variation in REER in both country clusters.
Keywords: Real effective exchange rates; total factor productivity; financial development; high-income countries; middle-income countries